Mapping genes for stem rust and Russian wheat aphid resistance in bread wheat (Triticum aestivum) - Wessels, Willem Gerhardus (Stellenbosch : Stellenbosch University, 2012)
Thesis ( MScAgric) -- Stellenbosch University, 1997.